Influence of pyrolysis conditions on the adsorbent properties of hazelnut shell biochar to remove paracetamol, amoxicillin, and triclosan - Paula Madariaga-Segovia; Cristina A. Villamar-Ayala; Norma Ramos; Margarita Sánchez-Domínguez; Roberto Lavín (Case Studies in Chemical and Environmental Engineering)
This study optimized the production of biochar from hazelnut shells for the adsorption of paracetamol, amoxicillin, and triclosan from water. Biochar was produced under 27 conditions (temperature: 500–900 °C, time: 0.5–2 h, particle size: 150–2000 μm). Physicochemical and instrumental analyses, as well as batch adsorption tests, characterized the samples. Temperature (900 °C) is the most significant factor influencing biochar properties and adsorption performance. Adsorption data fitted well with heterogeneous isotherm models, including the Sips model and multilayer/monolayer models. The maximum adsorption capacities for paracetamol, amoxicillin, and triclosan were 19.973, 2.992, and 2.678 mg/g, respectively. Biochar-based adsorption systems with water treatment applications will be scaled.